The Effect of Inquiry Learning with Scaffolding on Misconception of Light Material among Fourth-Grade Students (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
The purpose of this study is to determine the effect of Inquiry learning with scaffolding to decrease the percentage of light material misconception among fourth-grade students. The method used was Quasi-experimental with a non-equivalent control group design. The population was fourth-grade students of the Surya Buana Islamic Elementary School, Malang. The result of Anacova showed that for the â€œClassâ€ variable, the value of Significance (P-value) obtained was smaller than the Î± significance level of 0,006 0,05. Based on the results of the Anacova test it was concluded that there was a significant effect from the use of Inquiry learning with scaffolding to decrease the percentage of light material misconception in fourth-grade students of Surya Buana Islamic Elementary School, Malang. The average percentage of studentsâ€™ misconceptions in the experimental class at the initial conception was 38.7% and dropped to 15.4% in conception after inquiry learning with scaffolding. While the average percentage of studentsâ€™ misconceptions of control class at the initial conception was 37.8% and dropped became 22.7% at conception after conventional learning. The decrease in the percentage of studentsâ€™ misconceptions of the experimental class was greater than the control class by a difference of 10.7%. Further research is suggested to examine more deeply the effect of inquiry learning with scaffolding on process skill, learning achievement, and other aspects of learning that are likely to be developed in students.